How Might Consideration of Cell Polarity Affect Daily Therapeutic Practices? A Literature Review: Cell Polarity and Therapeutic Practice - Ravanbod, Hamid Reza (Galen Medical Journal, 2023)
Background: In addition to biochemical gradients and transcriptional networks, cell be-haviour is controlled by endogenous bioelectrical signals resulting from the action of ion channels and pumps. Cells are regulated not only by their own membrane resting potential (Vmem) but also by the Vmem of neighbouring cells, establishing networks through electrical synapses known as gap junctions. V mem is the primary factor in producing a polarity that can regulate cell assimilation of various substances. This article aimed to examine how cell polarity can change and how variations in cell polarity may lead to clinical demonstrations.Materials and Methods: Using Cochrane Central, PubMed, Scopus, Web of Sci-ence (WOS), and Embase, a comprehensive qualitative literature review was con-ducted from February 1, 2018, to February 1, 2023, to identify studies addressing bio-electric, cell polarity, and electroceuticals in patients with foot and ankle problems.Results: Out of 1,281 publications, 27 were included. One study investigated bioelectric wound-healing. Twenty-five studies examined bioelectric nerve cell growth, whereas one study evaluated bioelectricity-induced cellular differentiation in the treatment of arteriopathies.Conclusion: The author of this systematic review support addressing the predisposing fac-tors and healing impediments for a disease, thereby enhancing the healing process and re-ducing the likelihood of recurrence or parallel conditions. This method of treatment has pro-vided a summary of evidence indicating that cell polarity could be addressed for the treat-ment and prevention of most if not all, foot and ankle problems. However, owing to the limitations of V mem and bioelectricity measurement and the direct or indirect involvement of genetics and chemical gradients, further studies are required to confirm these results.